2019
DOI: 10.1155/2019/3168618
|View full text |Cite
|
Sign up to set email alerts
|

Ecofriendly Reduction of Methylene Blue with Polyurethane Catalyst

Abstract: A number of physical, chemical, and biological technologies have been developed to address the issue of synthetic dyes in wastewater. One of the important chemical methods involves reduction of these stringent pollutants into less hazardous products. In this study, a cross-linked polyurethane foam (CPUF) was prepared from toluene diisocyanate (TDI), tetraethylenepentamine (TEPA), and polycaprolactone diol (PCL; Mw: 1000 g/mole). To avoid harmful reducing agents, ecofriendly reduction of methylene blue (MB) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In addition to a weak peaks related to NCO at 2,260 cm −1. 35 …”
Section: Resultsmentioning
confidence: 99%
“…In addition to a weak peaks related to NCO at 2,260 cm −1. 35 …”
Section: Resultsmentioning
confidence: 99%
“…The amount of dye remaining without degradation in samples taken from a certain volume of dye solution containing ZrO2 at different time intervals was determined by UV-Vis spectrometry. For all experiments, the dye degradation percentage was calculated with Equation 1 [22,23]:…”
Section: Photocatalytic Activitymentioning
confidence: 99%
“…It has been reported that the optical energy band gap of zirconia as a direct band gap insulator varies between 3.0 and 5.7 eV, and the low band gap may be related to oxygen deficiency in wide band gap semiconductors [41]. Navio et al [22] reported an energy band gap of 3.65 eV for monoclinic ZrO2 powders prepared by adding an aqueous solution of zirconium oxychloride and ferric nitrate to pH=9-10 and drying the gel at 600ºC.These authors argue that the decrease in band gap energy as a result of the conditions used in the sol-gel technique can be attributed to a highly disordered structure. As a result of structural defects, some energy levels are introduced into the semiconductor band gap, allowing lower energy transitions, thus leading to a decrease in the band gap energy [42].…”
Section: Uv-vis Measurementsmentioning
confidence: 99%
“…Methylene blue (MB), which is the member of the thiazine class of dyes, is another heterocyclic aromatic industrial pollutant [118]. The ingestion of MB in human body has been reported to restrict oxidase enzymes in the body, which may lead to grave disorders, i.e., toxicity of the central nervous system, gastrointestinal infections and decolorization of the brain parenchyma [119,120]. During the reduction of MB, NaBH 4 acts as a reducing agent, and NPs act as an absorbent [121].…”
Section: Catalytic Properties Of Flower-derived Npsmentioning
confidence: 99%